إضواء وآراء حول واقع ومستقبل إدارة الموارد البشرية صعبة المراس في منظمات الأعمال - العنزي سعد علي; صالح احمد علي (Journal of Economics and Administrative Sciences, 2008)
The current researsh is aimed to pay attention on concept of human resources hard (Difficult) to manage. Such style of human resourcses has emerged to form anew challenge for busniess organizations. Management such human resources entails first determing incentives of their behaviour models. Analyzing these models will be important to strategical management of them from work. In nutshell, this researsh try to recommendation of contemporary literature about future of difficult (hard) human resources management.